2009
DOI: 10.1177/1359105309342290
|View full text |Cite
|
Sign up to set email alerts
|

Changing Nutrition, Physical Activity and Body Weight among Student Nurses and Midwives

Abstract: The study tested if effects of a planning intervention on fruit and vegetable consumption, physical activity and body weight may be moderated by self-efficacy. Student nurses and midwives (N = 182) were randomly assigned to the planning or the control condition. The intervention included action and coping plans and was followed by two booster sessions. Follow-up took place at two months after last booster session. The intervention affected fruit and vegetable intake. Additionally, body mass index of overweight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
1
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(97 citation statements)
references
References 19 publications
5
85
1
6
Order By: Relevance
“…Dietary behaviors may have a strong social dimension, because eating is usually done in a social context. The findings are also consistent with previous literature that has identified associations between self-efficacy, self-reported fruit and vegetable intake, and body mass index, underscoring the importance of self-efficacy for health outcomes (Luszczynska & Haynes, 2009). Our conclusions constitute a contribution to an understanding of the interplay between social resources and self-regulation in healthy nutrition that can guide future intervention studies.…”
Section: Limitations and Strengthssupporting
confidence: 89%
See 1 more Smart Citation
“…Dietary behaviors may have a strong social dimension, because eating is usually done in a social context. The findings are also consistent with previous literature that has identified associations between self-efficacy, self-reported fruit and vegetable intake, and body mass index, underscoring the importance of self-efficacy for health outcomes (Luszczynska & Haynes, 2009). Our conclusions constitute a contribution to an understanding of the interplay between social resources and self-regulation in healthy nutrition that can guide future intervention studies.…”
Section: Limitations and Strengthssupporting
confidence: 89%
“…The internal consistency of this measure was acceptable (Spearman-Brown's ρ = .63). This instrument has been found to be valid in several studies in different cultural contexts (Kreausukon et al, 2012;Lhakhang et al, 2014;Luszczynska & Haynes, 2009). …”
Section: Methodsmentioning
confidence: 95%
“…They also contrast with fi ndings of Luszczynska and Haynes (2009), which reported that self-effi cacy must be suffi ciently high for the plans to work. Self-effi cacy and PBC being conceptually distinct, this could raise the question of whether planning boosted self-effi cacy in people with low PBC.…”
Section: Discussioncontrasting
confidence: 48%
“…Thus, II interventions are expected to be more effective among highly motivated individuals. With respect to physical activity, however, mixed results were observed regarding the moderating effect of this variable and no clear conclusion could be drawn from previous research (Arbour & Martin Ginis, 2009;Budden & Sagarin, 2007;Conner, Sandberg, & Norman, 2010;De Vet, Oenema, Sheeran, & Brug, 2009;Luszczynska & Haynes, 2009). Also, according to the health action process approach (HAPA; Schwarzer, 1992), the action phase process should be strongly influenced by self-efficacy (Bandura, 1977).…”
mentioning
confidence: 84%